Insights into the interaction of human serum albumin with ionic liquids – Thermodynamic, spectroscopic and molecular modelling studies - Kowalska, Dorota; Dołżonek, Joanna; Żamojć, Krzysztof; Samsonov, Sergey A.; Maszota-Zieleniak, Martyna; Makowska, Joanna; Stepnowski, Piotr; Białk-Bielińska, Anna; Wyrzykowski, Dariusz (International journal of biological macromolecules, 2023)
Human serum albumin (HSA) effectively binds different types of low-molecular-weight compounds and thus enables their distribution in living organisms. Recently, it has been reported that the protein-ligand interactions play a crucial role in bioaccumulation processes and provide an important sorption phase, especially for ionogenic compounds. Therefore, the binding interactions of such compounds with proteins are the subject of an ongoing interest in environmental and life sciences. In this paper, the influence of some counter-ions, namely [B(CN)4]− and [C(CN)3]− on the affinity of the [IM1–12]+ towards HSA has been investigated and discussed based on experimental methods (isothermal titration calorimetry and steady-state fluorescence spectroscopy) and molecular dynamics-based computational approaches. Furthermore, the thermal stability of the resulting HSA/ligand complexes was assessed using DSC and CD spectroscopy. As an outcome of the work, it has been ascertained that the protein is able to bind simultaneously the ligands under study but in different regions of HSA. Thus, the presence in the system of [IM1–12]+ does not disturb the binding of [C(CN)3]− and [B(CN)4]−. The presented results provide important information on the presence of globular proteins and some ionogenic compounds in the distribution and bioaccumulation of ILs in the environment and living organisms.